Benefits of pervious concrete for urbanized habitats - Giuseppe Giunti; Daniel Miczek (Acta Polytechnica CTU Proceedings, 2022)
Pervious (draining) concrete is a new generation concrete which, for its structure, allows rainwater to enter the subsoil and at the same time is determining the final surface without the need for any additional layer. Pervious concrete allows to drain off up to 95 % of precipitation, which represents a significant contribution to ecology and sustainability. Therefore, its use is particularly suitable in city parks, bike paths, in the vicinity of apartment buildings, swimming pools and parking lots. Rainwater is not purposelessly be drained by the city sewer system, but it is absorbed directly in place and contributing to the environmental improvement of the urban habitat (replenishment of groundwater supplies, water for roots of plants and trees, reduction of the thermal island of the city, etc.). Unlike prefabricated paving blocks (interlocking and flat paving), pervious concrete makes it possible to realize structured and complex shapes of finished surfaces without the need for laborious cutting, waste, dust and with generally faster laying. This paper summarizes the current achievements within the Buzzi Unicem Group and the use of pervious concrete in the Czech and Slovak Republic.